(untitled) (Global Journal of Medical Research, 2018)
Endometrial thickness (ET) ultrasound measurement has high diagnostic performance for detection of endometrial cancer in symptomatic postmenopausal women. Identified clinical risk factors, Doppler or 3D ultrasound parameters to predict endometrial malignancy had been proposed in several studies. This article is comparing the accuracy of ultrasound endometrial thickness with scoring system/index involving both of clinical and ultrasound parameters to predict endometrial malignancy. Eight eligible diagnostic studies were appraised to assess the accuracy of ultrasound ET and/or ultrasound-based index to predict malignancy. The incidence of endometrial malignancy confirmed by histopathology examination was ranging from 10.5 to 58% from 8 studies. Ultrasound-based index to predict endometrial malignancy had good accuracy (AUC 75%-98%). The addition of endometrial volume/ uterine corpus volume ratio (EV/UCV) and Doppler to clinical parameters had increased the prediction accuracy of the index. While ultrasound ET alone has also high sensitivity, respectively 90.6% and 96.9% using the cut-off 4 mm and 3 mm with low accuracy.